Karakter Pendidik dan Peserta Didik - Yahya Zahid (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Indonesia faces many problems of education that should be understood and soived wiseiy. One ofthe ways to do so is by utitizing the classical thories and contextualizing them within lndonesian, global, and lslamic perspective. This paper focuses on elaborating the notion of ideal characters of theachers and students as promoted by Kitab Adab at- Alim wa at-Muta'altim written by KH Hasyim Asy'ari. This study is very important because of twc reasons. First, teachers and students are the most important element of education therefore to solve the probtem in conceptuatizing and building their personal characters means solving thethe major problem of education. Second, this book g'ives perspective of character building based on the context of Indonesia as well as Islam. Eventough the setting of this book is traditional era of Indonesia, the spirit of this book still relevan until nowdays after contextuatizing its notions within the recent context of Indonesia and Islam. As result, the notion of the book especially concerning on the ideal characters of teachers and students is still relevant for the recent conditions of education, esepecially religious education, in Indonesia by understanding it contextually. Keywords: Teacher, Student, Ethics of Study, and Ethics of Teaching.